2010
DOI: 10.1111/j.1469-0691.2009.02900.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacteraemia as a result of Campylobacter species: a population-based study of epidemiology and clinical risk factors

Abstract: Invasive disease as a result of Campylobacter is rarely reported. We reviewed 46 cases of blood stream infection with Campylobacter in a Danish population with complete follow-up. The incidence was 2.9 per 1 million person-years with a peak incidence in the age group above 80 years. In the population, the ratio of notified bacteraemia/enteritis patients with Campylobacter infection was 0.004. Patients with bacteraemia were older and had higher comorbidity, e.g. alcoholism, immunosuppression, previous gastroint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 14 publications
4
65
1
3
Order By: Relevance
“…For example, in a hospital-based study, Tee and Wijch reported a prevalence of 1.6% for bacteremia in persons infected with Campylobacter [60]. However, in background population-based studies, Campylobacter bacteremia was observed to be 5-10 times less abundant, with reported mortalities being between 2 and 13% [56]. Further, the clinical setting may also be responsible for the differences reported between C. jejuni-induced bacteremia and patient age.…”
Section: Surveillance Of Campylobacter Gastroenteritis and Bacteremiamentioning
confidence: 84%
See 2 more Smart Citations
“…For example, in a hospital-based study, Tee and Wijch reported a prevalence of 1.6% for bacteremia in persons infected with Campylobacter [60]. However, in background population-based studies, Campylobacter bacteremia was observed to be 5-10 times less abundant, with reported mortalities being between 2 and 13% [56]. Further, the clinical setting may also be responsible for the differences reported between C. jejuni-induced bacteremia and patient age.…”
Section: Surveillance Of Campylobacter Gastroenteritis and Bacteremiamentioning
confidence: 84%
“…Other studies from Finland and Denmark estimated the annual incidence of Campylobacter-related bacteremia to be 0.2-0.29/100,000 [53,56]. In these studies, it was estimated that for every 1000 gastroenteritis cases, three episodes of bacteremia could be detected, though this frequency may differ in hospitalbased populations.…”
Section: Surveillance Of Campylobacter Gastroenteritis and Bacteremiamentioning
confidence: 93%
See 1 more Smart Citation
“…Predisposing host risk factors described in the literature include male gender and the host immune status prior to bacterial exposure [25,26]. In a single centre study in Madrid, Spain, a total of 15 out of 64 cases (23%) of Campylobacter bacteraemia were in patients with known HIV infection [15].…”
Section: This Study Describes the Clinical And Epidemiological Featurmentioning
confidence: 99%
“…Bacteremia due to Campylobacter species has been considered rare; it was detected in less than 1% of patients with gastroenteritis due to these species (2). Therefore, the clinical features of bacteremia due to Campylobacter species have been the focus of several investigators and have yet to be fully elucidated (2)(3)(4)(5)(6)(7)(8)(9)(10). Most previous reports are from European countries and included data obtained from cases of bacteremia due to not only C. jejuni but also other Campylobacter species.…”
Section: Introductionmentioning
confidence: 99%